KECENDERUNGAN IDEOLOGIS TAFSIR KHILĀFAH DALAM AL-QUR’AN; ANALISIS TERHADAP PENAFSIRAN TĀHIR IBNU ‘ASHŪR DAN TAQIY AL-DĪN AL-NABHĀNĪ - ahmad nabil (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2020)
This article discusses the insight of the khilāfah in the perspective of Ibn Ashur and Taqī al-Dīn al-Nabhānī. This article departs from the problem that the khilāfah discourse continues to be a polemic among interpreters, especially when the khilāfah is associated with the state. From this problem, this article will discuss the concept of khilāfah in the perspective of T}āhir Ibn Ashur and Taqiy al-Dīn al-Nabhāni. Although al-Nabhānī does not have a complete interpretation work like Ibn Ashur, he does interpret the khilāfah verses contained in his works. Both are sunni figures, although in their attitude towards the problems of the state and khilafah they are different. This article questions how Ibn Ashur and al-Nabhāni view the interpretation of the khilāfah verse? And what are the implications of the two interpretations of the Indonesian context? By using a thematic interpretation approach and discourse analysis of the two interpretive works, this study comes to the conclusion that; (1) khilāfah according to Ibn Ashur is the name of leadership that embodies the leadership of the prophet. while Taqiy al-Dīn al-Nabhānī stated that the khilāfah of the leadership system of Muslims throughout the world is to uphold Islamic law and carry Islamic preaching to all corners of the world. The difference between the two figures in understanding the caliphate is, first, the arguments used by Ibn 'Ashūr emphasize more on aspects that are prerequisites for the Caliph in his khilafah, such as those who believe and do good deeds do justice, while Taqiy al-Dīn al-Nabhānī is more leads to the obligation to obey and practice what Allah commands, and the obligation to establish a caliphate. Second, that both of them have differences in the realm of ideology, of course this will have little or much impact on the frame of mind of the two figures, so what the authors find that distinguishes the two figures is that Ibn 'Ashur is more moderate than Taqiyuddin An-Nabahni.